The strategic synergy of educational psychology and managerial practices for the efficient development of educational institutions - Khaoula Khennou; Bouzekri Touri (Journal of Education and Health Promotion)
BACKGROUND: The mental health of the educational community is a crucial aspect that needs to be addressed. In this context, educational psychology is an important lever in all areas, particularly in educational management. The main aim of this study is to determine the significance between educational psychology and educational managerial aspects. MATERIALS AND METHODS: A quantitative approach, grounded in a non-experimental and correlational investigation. We focused on variables that constitute particular facets of educational management in synergy with educational psychology. The sample was based on 96 qualifying secondary school principals in the Casablanca-Settat region of Morocco. Data collection was based on school principals’ responses to a questionnaire. Data processing was carried out using IBM SPSS Statistics 29 software, with an overall significance of 62.5% for the correlations processed. Our study is recent and topical, as it took place in 2023. RESULTS: The results reveal a significant relationship between the educational psychology variable and the stress management aspect variable, with an effect size of 25.8%, as well as with the human resources management aspect, with an effect size of 23.4%, and also a large effect size of 32.1% with the adaptation to change aspect. Among other things, a significant effect size of 45.8% was noted between the educational psychology variable and the school climate aspect. Finally, the relationship between the dependent educational psychology variable and the independent continuing education variable showed a significant effect size of 25.1%. CONCLUSIONS: It is essential to emphasize the importance of combining managerial aspects and educational psychology to promote mental health and optimize the functioning of schools and the performance of education systems in general.